Effects of Dietary Vitamin C Supplementation on Feed Intake and Growth Performance of Nile Tilapia (Oreochromis niloticus) - Kriama Tutkey; Dwi Indah Widya Yanti (INTEGRATED OF FISHERIES SCIENCE, 2025)
Vitamin C plays an essential role in maintaining immune function, reducing stress, accelerating wound healing, and supporting collagen synthesis in fish. Adequate dietary vitamin C supplementation can enhance nutrient utilization and promote fish growth and survival. This study aimed to evaluate the effect of dietary vitamin C supplementation on the growth performance and feed utilization of Nile tilapia (Oreochromis niloticus) and to determine the optimal dosage for growth enhancement. The study employed an experimental method using a Completely Randomized Design (CRD) consisting of four treatments and three replications. The treatments consisted of a control diet (without vitamin C supplementation) and diets supplemented with vitamin C at levels of 0.5%, 1.0%, and 1.5%. The observed parameters included absolute weight gain, specific growth rate (SGR), daily growth rate, absolute length gain, feed conversion ratio (FCR), feed efficiency (FE), and survival rate (SR). The results showed that dietary vitamin C supplementation significantly improved growth performance, feed efficiency, and survival of Nile tilapia (p<0.05). The best performance was obtained in the treatment containing 1.5% vitamin C, resulting in an absolute weight gain of 2.16 g, specific growth rate of 1.6% day⁻¹, daily growth rate of 0.05 g day⁻¹, absolute length gain of 4.97 cm, feed conversion ratio of 0.94, feed efficiency of 91.80%, and survival rate of 100%. However, the differences in feed conversion ratio were not statistically significant (p>0.05). In conclusion, dietary vitamin C supplementation enhanced growth performance, feed utilization efficiency, and survival of Nile tilapia. The optimal dosage observed in this study was 1.5% vitamin C supplementation in the diet..